Surveillance of Antimicrobial Resistance in Iraq: A Comprehensive Data Collection Approach - Al-Fahad, Dhurgham K.; Alpofead, Jawad A.; Chawsheen, Mahmoud A.; Al-Naqshbandi, Ahmed A.; Abas, Ali T. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Antimicrobial resistance (AMR) generates serious negative impacts on health-care systems worldwide, and Iraq is not an exception. To uncover the prevalence of AMR and to visualize the magnitude of the multidrug-resistant (MDR) dilemma in Iraqi hospitals, this study is carried out. A total of 11592 clinical records from ten different health-care facilities in seven Iraqi provinces are collected and analyzed. Our data show that 4984 (43.0%) of all clinical samples are negative for bacterial growth. In adults, Gram-negative bacteria (GNB) represented 48.9% and Gram-positive bacteria (GPB) represented 51.1% of clinical isolates; in children, GNB represented 60.8% and GPB represented 39.2%. Furthermore, in adults, Klebsiella pneumoniae (30.1%) and Staphylococcus aureus (40.8%) are among the most common GNB and GPB isolates, respectively. In children, K. pneumoniae (37.9%) and Staphylococcus haemolyticus (41.8%) are the most common GNB and GPB, respectively. Adults’ samples showed that Escherichia coli and Proteus mirabilis were the most resistant GNB; S. aureus and Staphylococcus epidermidis are among the most resistant GPB. In children, K. pneumoniae is found to be the most resistant GNB. This study confirms the persistence of antimicrobial resistance and multidrug-resistant gram-negative and gram-positive bacteria in adults and children alike. Ampicillin and oxacillin have been recognized as ineffective drugs in adults, and ampicillin, nafcillin, cefoxitin, and benzylpenicillin have been found to be highly resisted by pathogenic bacteria in children. The outcomes confirm the necessity of conducting AMR surveillance on a regular basis and establishing national antibiotic prescription guidelines to manage AMR development in Iraq.